Pengaruh Pendidikan Kesehatan Gigi Dan Mulut Melalui Media Audio Taktil Terhadap Status Kebersihan Mulut Penyandang Tunanetra Balai Rehabilitasi Sosial Bhakti Candrasa - Lathief, Abdul Ghani, Dwi Kurniawati, S.KG, MPH (2016)
Background: Visual impairment often have worse in oral hygiene status than the general population . They tend to have a higher prevalence of caries because of barriers to access health care and less information about teeth and mouth.Visual Impairment should be given equal opportunities in obtaining dental and oral hygiene education as people in general in accordance with the power of arrest information held in order to achieve good oral hygiene. Therefore, special media required in the process of oral health education so that blind people are able to understand the material presented to the fullest. Media are effectively used to blind the received information is audio tactile media due to receive their information to maximize hearing and to accept their new skills utilizing tactile sensations. Objective: The purpose of this study was to influence oral health education through the medium of audio tactile towards oral hygiene status with visual impairment Balai Rehabilitasi Sosial Bhakti Candrasa.Methods:This study is a quasi-experimental research with pretest and posttest only design. The subject of research is 31 blind category. Subject examination and measurement of plaque score before the intervention using PHP-M, then intervention in the form of oral and dental health education using tactile audio media for one week, later examination and measurement of plaque score at the end.Result: The results of the study resulted in a mean before and after dental health education using audio tactile media are 17.29 and 9.42 . The decline in the average plaque scor occur between before and after dental health education using audio tactile media . Results of the study resultedin significant value of p = 0.000 (p <0.05) between plaque scores before and after the plaque scores were given oral health education using tactile audio media. Conclusion: that oral health education using audio tactile media effect on risng oral hygiene visual impairement inBalai Rehabilitasi Sosial Bhakti Candrasa.